Bile salts and calcium absorption - Webling, D. D'A. (1966)
1. The study of the effect of bile salts on enhancing calcium absorption in the rachitic chick has been extended to bile salts not present in chick bile, e.g. glycine conjugates and bile alcohol sulphates. 2. Bile and bile salts cause an increase in calcium absorption from sparingly soluble calcium hydrogen phosphate when compared with a suspension of calcium hydrogen phosphate in saline. 3. If the bile ducts of normal rats are tied the absorption of calcium from calcium hydrogen phosphate decreases but can be restored by giving bile salts with the calcium salt. 4. Bile salts increase solubility in water of the sparingly soluble calcium salts, phytate and phosphate at pH values between 6 and 8. 5. Bile salts increase the solubility in lipid solvents of calcium in approximately the same proportion as they increase the absorption of calcium from the gut. 6. The physiological role of bile in calcium absorption and its mode of action are discussed.